Sistem Kurikulum Amerika Serikat dalam Perspektif Pendidikan Abad 21 - Heriyana, Tio; Waluya, St Budi; Mulyono, Mulyono (Papanda, 2026)
This study aims to analyze the United States curriculum system in the context of 21st-century education through a library research approach. This study examines in depth the basic principles, structure, policy dynamics, and implementation of 21st-century skills in the United States education system. The results show that the United States curriculum system is decentralized, flexible, and oriented toward competency development. The federal government acts as a policy and funding facilitator, while states and school districts have full autonomy in designing and implementing curricula according to the local context. Policy reforms through the No Child Left Behind Act (NCLB), Every Student Succeeds Act (ESSA), and Digital Equity Act mark a paradigm shift from test-based education to competency-based, technology-based, and socially equitable education. The U.S. curriculum emphasizes the integration of 21st-century skills, including critical thinking, creativity, communication, collaboration, as well as project-based learning, digital technology, and personalized learning. The findings also show that the flexibility of this system is both a strength and a challenge, as it causes quality gaps between regions due to differences in local resources. In the Indonesian context, the results of this study provide inspiration for strengthening the Merdeka Curriculum by emphasizing responsible decentralization, competency-based innovation, and equitable national education quality. Conceptually, this study confirms that the 21st-century curriculum must be designed as an adaptive learning ecosystem that combines local freedom, pedagogical innovation, and social responsibility.